Africa Agriculture Science Week is a place for knowledge sharing opportunities - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Alhoji Muhamed Sanal says that #AASW6 is a very important place for knowledge sharing opportunities The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/africa-agriculture-science-week-2013/ http://www.fara-africa.org/scienceweek/